Profibrogenic macrophage-targeted delivery of mitochondrial protector via exosome formula for alleviating pulmonary fibrosis - Wei Zhang; Zhuo Wan; Di Qu; Wenqi Sun; Liang Zhang; Yuan Liang; Lei Pan; Hua Jiang; Zichen Ye; Mengying Wei; Lijun Yuan; Guodong Yang; et al. (Bioactive Materials, 2024)
Pulmonary fibrosis (PF) is a devastating lung disease with limited treatment options. During this pathological process, the profibrogenic macrophage subpopulation plays a crucial role, making the characterization of this subpopulation fundamentally important. The present study revealed a positive correlation between pulmonary macrophages with higher mitochondrial mass (Mømitohigh) and fibrosis. Among the Mømitohigh subpopulation of CD206+ M2, characterized by higher expression of dynamin 1-like (Drp1), as determined by flow cytometry and RNA-seq analysis, a therapeutic intervention was developed using an exosome-based formula composed of pathfinder and therapeutics. A pathfinder exosome called “exosomeMMP19 (ExoMMP19)”, was constructed to display matrix metalloproteinase-19 (MMP19) on the surface to locally break down the excessive extracellular matrix (ECM) in the fibrotic lung. A therapeutic exosome called “exosome therapeutics (ExoTx)”, was engineered to display D-mannose on the surface while encapsulating siDrp1 inside. Prior delivery of ExoMMP19 degraded excessive ECM and thus paved the way for ExoTx to be delivered into Mømitohigh, where ExoTx inhibited mitochondrial fission and alleviated PF. This study has not only identified Mømitohigh as profibrotic macrophages but it has also provided a potent strategy to reverse PF via a combination of formulated exosomes.